Hematological reference parameters of indigenous guinea pigs (Cavia porcellus) - Oriundo Núñez, Katherine Patricia (2021)
The present study aimed to determine the haematological parameters of indigenous guinea pigs in the Ayacucho area, Peru, taking into account age, sex and physiological status (pregnancy, lactating, weaned). Blood samples were taken and analysed manually following routine laboratory methods. The red blood cell count and haematocrit and haemoglobin values were higher in guinea pigs of the lactating stage compared to weaned animals, and in males as compared to females. Likewise, the red blood cell count and the haematocrit and haemoglobin values of pregnant females were like those of lactating guinea pigs. In the leukocyte formula, lymphocytes had the highest frequency, followed by neutrophils. The reference values reported in the different age groups and physiological status will allow better clinical decisions to be made.